Prediction of surgical complications in the elderly: Can we improve outcomes? - Preeya K. Mistry; Geoffrey S. Gaunay; David M. Hoenig (Asian Journal of Urology)
As the number of Americans aged 65 years and older continues to rise, there is projected to be a corresponding increase in demand for major surgeries within this population. Consequently, it is important to utilize accurate preoperative risk stratification techniques that are applicable to elderly individuals. Currently, commonly used preoperative risk assessments are subjective and often do not account for elderly-specific syndromes that may pose a hazard for geriatric patients if not addressed. Failure to accurately risk-stratify these patients may increase the risk of postoperative complications, morbidity, and mortality. Therefore, we aimed to identify and discuss the more objective and better-validated measurements indicative of poor surgical outcomes in the elderly with special focus on frailty, patient optimization, functional status, and cognitive ability.